DISPARITY OF LEGAL CULTURE AND SOCIAL IDENTITY CRISIS IN INTER-RELIGIOUS MARRIAGE. (CASE STUDY OF MEPAMIT CUSTOM IN THE VIEW OF RELIGIOUS FIGURES IN PETANG VILLAGE, BADUNG, BALI.) - Jessica Aulia; Gandhung Fajar Panjalu; Mohammad Ikhwanuddin (RADJA PUBLIKA, 2025)
This study aims to examine the position of the mepamit custom in Indonesian marriage law and to understand the views of religious leaders on the implementation of this tradition in the context of interfaith marriage in Petang Village, Badung Regency, Bali. Mepamit is a traditional procession in Balinese Hindu society that functions as a request for spiritual permission to ancestors when someone wants to change religions due to interfaith marriage. This study uses a qualitative approach with case study methods, in-depth interviews, and participatory observation. The results of the study indicate that mepamit has a position as a living customary law and plays an important role in maintaining the continuity of spiritual relationships between individuals and their ancestors. Hindu religious leaders emphasize that this procession is a moral and spiritual obligation, while Islamic religious leaders show a tolerant attitude as long as its implementation does not violate the principles of faith. These findings show that mepamit is a symbol of reconciliation between individual freedom and collective values, and reflects the practice of functional tolerance in a multicultural society. This study contributes to strengthening legal pluralism in Indonesia and provides new understanding of the role of customary law in contemporary socio-religious dynamics.